Charles Frederick Thomas papers - Thomas, Charles Frederick, 1817 or 1818-
Correspondence, contracts, and a photocopied broadside of a speech relating to Thomas's work as chief machinist and supervisor of construction for the U.S. Capitol expansion and dome; patent, mechanical drawings, and clipping regarding locomotives and streetcars; and proof of citizenship (1837), will (1889), letter (1865) describing Lincoln's inauguration, and other personal items.
Mechanical engineer in the U.S. Office of the Architect of the Capitol.
Library of Congress Rare Book and Special Collections Division.
Library of Congress Prints and Photographs Division.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Lincoln, Abraham, -- 1809-1865 -- Inauguration, 1865.; United States. -- Architect of the Capitol; United States Capitol (Washington, D.C.); Architecture; Electric railroads -- Cars; Locomotives; Mechanical engineering; United States -- Capital and capitol; Engineers